Impact of Financial Technology (Fintech) Evolution on the Profitability of Banks in Pakistan - Khan, Badar Farooq (2020)
The research investigates the impact of financial technology and bank-specific variables on the scheduled banks of Pakistan. The analysis is conducted from 2010-2019 in which the banking sector of Pakistan has started to transform itself through technological innovations in its operational module. However, in a developing country such as Pakistan, financial technology (Fintech) models are mainly restricted to only e-banking which includes; mobile banking applications, real-time online banking (RTOB's), point of sale transactions and automated teller machines (ATM's). Due to limited penetration and adoption of financial technology, the impact of fintech in enhancing banks profitability is yet to be measured and analyzed in Pakistan. The analysis of this research is based on a strongly balanced panel data over a period ranging from 2010-2019 for the banking sector of Pakistan. Profitability indicators are measured through return-on assets (ROA) and profit margins (PM), whereas e-banking value and automated-teller machines transactions are used as fintech-specific variables. Further, we added bank-specific as controlled variables such as asset size, liquidity, credit quality, operational efficiency, solvency and banking sector development which directly impacts the profitability of the traditional banking system. This study also checks the effect of bank and fintech alliance on the performance of the banking industry by creating a dummy variable. For the analysis, we selected the fixed-effect model followed by a robustness check after running the Hausman test. The results of our study are consistent and aligned with the previous empirical results regarding the profitability determinants and financial technology in the banking industry.